ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI KONTRIBUSI PAJAK KENDARAAN BERMOTOR (PKB) TERHADAP PENDAPATAN ASLI DAERAH (PAD) DI KABUPATEN KUTAI TIMUR - Ahmad Dani (ADMINISTRASI PUBLIK, 2019)
Tax is a mandatory contribution collected by the government from the community (taxpayer) to cover the state's routine expenses and development costs without remuneration that can be directly appointed. Motorized vehicle tax is a tax on the ownership and / or control of motorized vehicles, all wheeled vehicles and their vehicles used on all types of road and movement by technical equipment. The formulation of the problem is 1). How big is the contribution of Motor Vehicle Tax (PKB) to Regional Original Income (PAD) in East Kutai District ... 2). What are the obstacles and difficulties in the field in the process of citing Motor Vehicle Taxes (PKB) in East Kutai Regency. The type of data used in this study is secondary data types. Secondary data is data obtained both unprocessed and processed, either in the form of numbers or in the form of description. In this study secondary data taken from the literature relevant to research titles such as books, magazines, articles, time / period of technical instructions and others that have relevance to the problem under study.The results of the study show the contribution of motor vehicle tax (PKB) to original income. The lowest area in 2013 of 12.90% was included in the low or low category. Thus the contribution or benefits provided by the acceptance of Motor Vehicle Tax (PKB) on Regional Original Income in 2013-2017 is still low. However, Regional Original Income is not only influenced by the acceptance of Motor Vehicle Tax (PKB), because there are still other income receipts that can affect Regional Original Income (PAD